Академік Андрій Михайлович Гродзінський — істини алелопатії (до 85-річчя від дня народження вченого) - Мусатенко, Л.І.; Мусієнко, М.М.; Ситник, К.М. (Український ботанічний журнал, 2012)
В статье освещены основные этапы жизни, научной и научно-организационной деятельности известного ботаника и физиолога растений – академика АН УCCP, доктора биологических наук, профессора А.М. Гродзинского. The article covers the main stages and milestones of life and research activities of the renowned botanist and plant physiologist, Academician of the Academy of Sciences of the UkrSSR, Professor A.M. Grodzinsky.